Hybrid Gravimetry to Map Water Storage Dynamics in a Mountain Catchment - Chaffaut, Quentin; Lesparre, Nolwenn; Masson, Frédéric; Hinderer, Jacques; Viville, Daniel; Bernard, Jean-Daniel; Ferhat, Gilbert; Cotel, Solenn (Frontiers in Water, 2022)
In mountain areas, both the ecosystem and the local population highly depend on water availability. However, water storage dynamics in mountains is challenging to assess because it is highly variable both in time and space. This calls for innovative observation methods that can tackle such measurement challenge. Among them, gravimetry is particularly well suited as it is directly sensitive to changes in soil water content occurring at an intermediate spatial scale, which is consistent with water redistribution processes occurring in mountain hydrosystems. To provide constrains on water storage changes in a small headwater catchment (Strengbach catchment, France), we implemented a hybrid gravity approach combining in-situ precise continuous gravity monitoring using a superconducting gravimeter, with relative time-lapse gravity made with a portable Scintrex CG5 gravimeter over a network of 16 stations. This paper presents the resulting spatio-temporal changes in gravity and discusses them in terms of spatial heterogeneities of water storage. We interpret the spatio-temporal changes in gravity by means of the topographic wetness index and, for the first time to our knowledge in a mountain context, by means of a physically based distributed hydrological model. This study therefore demonstrates the ability of hybrid gravimetry to assess the water storage dynamics in a mountain hydrosystem and shows that it provides promising observations to constrain a physically based distributed hydrological model.